Bootstrap Methods and Applications in Econometrics - A Brief Survey - Pål Bergström (Uppsala University, Department of Economics, 1999)
This paper provides a brief survey of the bootstrap and its use in econometrics. As an introduction, the paper gives a description of the basics of the method, with a special emphasis on boostrap testing. A fairly large amount of space is devoted to discuss why bootstrap tests provide refinements compared to equivalent asymptotic tests. A series of recent different applications in the econometrics literature is then surveyed, in order to give a picture of this rapidly evolving research field.
urn:nbn:se:uu:diva-2440
Keywords: C40; 330; Bootstrap; Sample Reuse Methods; Simulation Methods; Theorie; Bootstrap-Verfahren